ANALISIS KOMPARATIF KINERJA KEUANGAN PT SUMBER ALFARIA TRIJAYA TBK DAN PT INDOMARCO PRISMATAMA BERDASARKAN ANALISIS RASIO PROFITABILITAS DAN RASIO SOLVABILITAS PERIODE 2020-2022 - Vandera, Canasia; Oktalina, Gayatria; Shinta Lestari, Deara (Jurnal Akuntansi Bisnis Dan Keuangan, 2024)
This research aims to analyze and compare financial performance based on Profitability Ratios and Solvency Ratios between PT Sumber Alfaria Trijaya (Alfamart) and PT Indomarco Prismatama (Indomaret) in 2020 to 2022. This research is descriptive qualitative research using documentation and literature study techniques. The ratio analysis method used is Gross Profit Margin (GPM), Return on Equity (ROE), Return on Investment (ROI), Debt to Asset Ratio (DAR) and Debt To Equity Ratio (DER). From the research results, it is known that the comparison of the performance of PT Sumber Alfaria Trijaya (Alfamart) with PT Indomarco Prismatama (Indomaret) shows a ratio value that is not good, but continues to increase every year. However, to compare the two companies, it shows that PT Sumber Alfaria Triaya (Alfamart) is superior to PT Indomarco Prismatama (Indomaret) in terms of the Profitability Ratio. Comparing the financial performance of PT Sumber Alfaria Trijaya Tbk and PT Indomarco Prismatama based on the Solvency Ratio, it is clear that PT Sumber Alfaria Trijaya Tbk and PT Indomarco Prismatama are both doing well. However, for the DAR and DER ratio in 2020 and 2021, PT Sumber Alfaria Trijaya Tbk is superior to PT Indomarco Prismatama. Meanwhile, in DAR and DER in 2022, PT Indomarco Prismatama is superior to PT Sumber Alfaria Trijaya Tbk.